Risk Management in South Asia : A Poverty Focused Approach - World Bank (Washington, DC, 2013)
In recognition that poverty and vulnerability are mutually reinforcing, because the poor lack the ability to insure against risks, often shaping behavior and decision making to minimize exposure to risks, even at the cost of economic efficiency, and long-term interest, this paper reviews what is known about the risk-coping, and risk-mitigating behavior of the poor in South Asia. It examines the support received from the governments, and nongovernmental organizations, as well as the Bank's contributions, and, presents suggestions for a strategy to reduce poverty, and efforts to overcome risk. Analytical work classifies the risks that threaten different vulnerable groups, or poor households, according to poverty incidence and severity, and, a similar effort evaluates both the risk-reducing impact of anti-poverty programs, and the performance and potential of less traditional approaches, such as micro-finance. On assessing government programs, the study evaluates the role, impact, and potential of policy mechanisms, or strategies commonly used in the region, reviewing welfare programs in public works, transfers in cash or kind, innovative programs for savings and insurance services, and pension reforms, as well as how to expand such programs. The study argues on the need for a comprehensive social protection strategy that can address both poverty, and vulnerability, identifying the priorities of vulnerable groups, and specific risks, to then develop an implementation structure, and institutional reforms that expand market opportunities which facilitate formal mechanisms for risk management.